2022
DOI: 10.34256/ijpefs2223
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Temporal Gait Parameters When Walking on Even Surface Walkway, Treadmill, and Pushing a Constant Resistant Sled

Abstract: Motorized treadmills and weighted sleds are employed in clinical settings to improve lower extremity strength, power, and endurance. However, little is known about how the spatio-temporal parameters compare when walking on an even surface walkway, walking on a treadmill, or pushing a sled. This study aimed to examine the variations in spatial and temporal gait parameters when walking on an even surface walkway (EW), on a treadmill (TW), and while pushing a sled (SP). Forty healthy subjects participated in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, a study by Wall-Scheffler et al (2010) showed an increase in rectus femoris activation compared to the hamstrings during increases in inclination during walking at a constant speed. The above led us to consider that people demonstrate varying muscle recruitment strategies at different speeds, changes in inclination, and surfaces, as mentioned by Rosario and Orozco (2022). Nevertheless, at similar speeds, inclinations, and surfaces, it seems the lower limb musculature patterns are comparable, as shown by the results of this study and the outcomes of Orozco et al (2022).…”
Section: Discussionmentioning
confidence: 50%
“…However, a study by Wall-Scheffler et al (2010) showed an increase in rectus femoris activation compared to the hamstrings during increases in inclination during walking at a constant speed. The above led us to consider that people demonstrate varying muscle recruitment strategies at different speeds, changes in inclination, and surfaces, as mentioned by Rosario and Orozco (2022). Nevertheless, at similar speeds, inclinations, and surfaces, it seems the lower limb musculature patterns are comparable, as shown by the results of this study and the outcomes of Orozco et al (2022).…”
Section: Discussionmentioning
confidence: 50%